The Effect of Vitamin D Supplementation on Subcutaneous Allergen Immunotherapy in House Dust Mite Sensitive Asthmatic Children - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (TURKISH SOC IMMUNOLOGY, 2015)
Objectives: This study aims to investigate the efficacy, safety, and T regulatory cell response of vitamin D supplementation concomitantly used with allergen specific immunotherapy (SIT). Materials and methods: Fifty children (29 girls, 21 boys; mean age 8.8 +/- 2.4 years) with asthma sensitized to house dust mite receiving pharmacotherapy were randomized into three groups as: subcutaneous immunotherapy in combination with vitamin D supplementation group (650 U/day; n=\17), subcutaneous immunotherapy group (n=\15) and pharmacotherapy group (n=\18). All patients were evaluated at baseline, 6 and 12 months for the symptom frequency, medication need, skin prick test, levels of serum vitamin D, total immunoglobulin E (IgE), specific IgE, and Der p 1-specific IgG4 levels. Dermatophagoides pteronyssinus induced CD4(+)CD25(+)Foxp3(+) T regulatory cell ratio, intracellular Foxp3 expression, and peripheral blood mononuclear cell interleukin 10 (IL-10) and transforming growth factor beta responses were assessed. Results: Concomitant use of vitamin D as an adjunct to allergen SIT reduced asthma symptoms compared to the others at six months. The need for corticosteroids also decreased, compared to the pharmacotherapy group. The baseline vitamin D levels were inversely correlated with the asthma attack number of the subsequent year. At one year, vitamin D supplemented subjects demonstrated a higher percentage of Der p 1-induced CD4(+)CD25(+)Foxp3(+) regulatory T cell ratio and IL-10 levels in lymphocytes, compared to other groups. Der p 1-specific IgG4 increased in both SIT groups and the increase was observed as an earlier surge at six months in vitamin D supplemented group. Conclusion: Concomitant use of SIT and vitamin D improved asthma control and reduced the inhaled corticosteroid need at an earlier stage. This beneficial clinical effects were accompanied by an increased ratio of Der p 1-induced T regulatory cells and expression of Foxp3.
Keywords: Allergy; asthma; immunotherapy; vitamin D; GRASS-POLLEN IMMUNOTHERAPY; REGULATORY T-CELLS; D DEFICIENCY; INDUCTION; CYTOKINES; EFFICACY; D-3